2009
DOI: 10.1103/physrevb.80.161310
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent transport in a sixfold degenerate two-dimensional electron system on a H-Si(111) surface

Abstract: Low-field magnetotransport measurements on a high-mobility ͑ = 110, 000 cm 2 / Vs͒ two-dimensional electron system on a H-terminated Si͑111͒ surface reveal a sixfold valley degeneracy with a valley splitting Յ0.1 K. The zero-field resistivity xx displays strong temperature dependence for 0.07Յ T Յ 25 K as predicted for a system with high degeneracy and large mass. We present a method for using the low-field Hall coefficient to probe intervalley momentum transfer ͑valley drag͒. The relaxation rate is consistent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…When the direction of the magnetic field B is tilted, the orbital LL splitting is given by the field component B ⊥ normal to the two-dimensional electron system (2DES) while the total field strength B determines the Zeeman splitting E Z . Early experiments on GaAs revealed that the ν = 4/3, 5/3, and 8/5 states behaved differently upon tilting the sample [4,5]: While the ν = 4/3 and 8/5 states were undergoing a transition from a spinunpolarized state to a polarized one, the ν = 5/3 state was always fully spin polarized.Although the FQHE has been reported in quite a number of different materials [6][7][8][9][10][11][12], the FQHE has never been observed in a diluted magnetic semiconductor in which atoms with magnetic moment (e.g., Mn 2+ ) are placed in a 2DES. Then, the localized spins in the magnetic impurities' d orbitals interact with the correlated electron system via the quantum mechanical s-d exchange interaction, causing giant Zeeman splitting [13] which is tunable in magnitude, sign, and field dependence [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When the direction of the magnetic field B is tilted, the orbital LL splitting is given by the field component B ⊥ normal to the two-dimensional electron system (2DES) while the total field strength B determines the Zeeman splitting E Z . Early experiments on GaAs revealed that the ν = 4/3, 5/3, and 8/5 states behaved differently upon tilting the sample [4,5]: While the ν = 4/3 and 8/5 states were undergoing a transition from a spinunpolarized state to a polarized one, the ν = 5/3 state was always fully spin polarized.Although the FQHE has been reported in quite a number of different materials [6][7][8][9][10][11][12], the FQHE has never been observed in a diluted magnetic semiconductor in which atoms with magnetic moment (e.g., Mn 2+ ) are placed in a 2DES. Then, the localized spins in the magnetic impurities' d orbitals interact with the correlated electron system via the quantum mechanical s-d exchange interaction, causing giant Zeeman splitting [13] which is tunable in magnitude, sign, and field dependence [14].…”
mentioning
confidence: 99%
“…Although the FQHE has been reported in quite a number of different materials [6][7][8][9][10][11][12], the FQHE has never been observed in a diluted magnetic semiconductor in which atoms with magnetic moment (e.g., Mn 2+ ) are placed in a 2DES. Then, the localized spins in the magnetic impurities' d orbitals interact with the correlated electron system via the quantum mechanical s-d exchange interaction, causing giant Zeeman splitting [13] which is tunable in magnitude, sign, and field dependence [14].…”
mentioning
confidence: 99%
“…A controllable way of occupying a particular spin state or filling a particular valley is a key ingredient, respectively, for spintronics 1 or valleytronics 2,3 aimed at the development of novel solid-state devices. The candidates appropriate for the realization of valleytronic concepts include multivalley semiconductors such as silicon, 2,4 graphene, 3,5,6 and carbon nanotubes. 2 A remarkable selective population of the electron states is achieved by optical pumping with polarized light: circularly for spin polarization 7 and linearly polarized for "valley polarization."…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14] Here we report on the vivid evidence of the existence of pure valley-orbit currents and demonstrate that the individual control of electron fluxes in valleys can be achieved by the excitation of (111)-oriented Si-metal-oxide-semiconductor (Si-MOS) structures with polarized light. Such two-dimensional systems contain six equivalent electron valleys 4,15 ( Fig. 1) and possess the overall point-group symmetry C 3v , that is, they are invariant with respect to the rotation by an angle of 120…”
mentioning
confidence: 99%
“…[5][6][7] For instance, at low temperature the magnetoresistance in a parallel magnetic field was measured for a low mobility sample. 3 A MIT at a critical density N MIT Ϸ 3 ϫ 10 11 cm −2 in a g v =2 Si͑111͒ was reported using a metaloxide-semiconductor field-effect transistor ͑MOSFET͒ for a sample with a peak mobility, at low temperatures, of peak Ϸ 2.5ϫ 10 3 cm 2 / Vs. 4 Recently grown samples, [5][6][7] made with hydrogen-passivated Si͑111͒/vacuum ͓H-Si͑111͔͒ structures, had higher mobility Ϸ 2.4ϫ 10 4 cm 2 / Vs with g v =2 at low electron density and with g v = 6 at high electron density. 6 Very recently a still higher mobility Ϸ 10 5 cm 2 / Vs together with a MIT at N MIT Ϸ 0.9 ϫ 10 11 cm −2 and a valley degeneracy g v = 6 was found with H-Si͑111͒ samples.…”
mentioning
confidence: 99%